2005
DOI: 10.1097/01.hp.0000160545.46907.fe
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Cog and McNp Codes in Computational Neutron Capture Therapy Modeling, Part Ii: Gadolinium Neutron Capture Therapy Models and Therapeutic Effects

Abstract: The goal of this study was to evaluate the COG Monte Carlo radiation transport code, developed and tested by Lawrence Livermore National Laboratory, for gadolinium neutron capture therapy (GdNCT) related modeling. The validity of COG NCT model has been established for this model, and here the calculation was extended to analyze the effect of various gadolinium concentrations on dose distribution and cell-kill effect of the GdNCT modality and to determine the optimum therapeutic conditions for treating brain ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Most therapeutic protocols are now based on molecular boron compounds [151]. However, different groups have reported the possibility to take advantage of ␥ -ray emission and Auger electrons of gadolinium isotopes ( 155 Gd and 157 Gd) upon interaction with a thermal neutron [136,[152][153][154][155]. In particular, the in vitro study of Bridot and colleagues showed the therapeutic potential of hybrid nanoparticles combining high contrast properties and long blood half-life [131] and a size (7 nm in diameter) compatible with partial extravasation from the vasculature and cell targeting.…”
Section: Conclusion and Outcomementioning
confidence: 99%
“…Most therapeutic protocols are now based on molecular boron compounds [151]. However, different groups have reported the possibility to take advantage of ␥ -ray emission and Auger electrons of gadolinium isotopes ( 155 Gd and 157 Gd) upon interaction with a thermal neutron [136,[152][153][154][155]. In particular, the in vitro study of Bridot and colleagues showed the therapeutic potential of hybrid nanoparticles combining high contrast properties and long blood half-life [131] and a size (7 nm in diameter) compatible with partial extravasation from the vasculature and cell targeting.…”
Section: Conclusion and Outcomementioning
confidence: 99%